Nation und Sprache: Die Diskussion ihres Verhältnisses in Geschichte und Gegenwart - Gardt, Andreas (de Gruyter, 2011)
Over the centuries, languages have played, and continue to play, a part in the political, cultural and ethnic definition of entities such as nation, empire or state.Using German as the main exemplar, but looking at other European languages as well, the book examines topics such as the geographical and demographic spread of languages, language and identity, language policy and legislation, language boundaries and political (and cultural and ethnic) boundaries, standard language and its varieties and the concept of a national language, linguistic and cultural patriotism.
Literaturangaben
Im Orig. ersch. 2000
Keywords: Geschichte; Electronic books; Aufsatzsammlung; Sprache; Nation; Ethnische Identität; Kulturelle Identität; Politische Identität; Deutsch